SUSTAINABILITY ORIENTED INNOVATION (SOI) IN DAGO POJOK CREATIVE VILLAGE IN BANDUNG CITY(PERSPECTIVE ACTOR NETWORK WITH APPROACH ACTOR NETWORK THEORY) - Anisia Br Sinamo, Hediyati
Skepticism that the current economic paradigm can overcome ongoing challenges in society, but faced with the fact that natural resources are dwindling. Innovation appears in development discussions as a means to improve the quality of life and change people's habits, one of which is sustainability-oriented innovation (SOI). Kampung Dago Corner is an urban village that reflects the City of Bandung as a Creative City. Kampung Dago Pojok is the first creative village in the city of Bandung. The Dago Pojok Creative Village phenomenon illustrates another context of sustainability-oriented innovation (SOI), which refers to innovation to achieve economic sustainability through efforts to minimize environmental degradation and social inequality. The SOI concept sees innovation and considers sustainability from a social, environmental and economic perspective, which is a process that involves interacting stakeholders. Some research has been conducted with regard to SOI implementation, but the previous research has mostly been conducted in business organizations and management, with little being discussed in non-profits and also in programs such as creative villages and tourism villages. The purpose of this research is to identify the role of actors in the development of Sustainability Oriented Innovation (SOI) in Creative Villages in Bandung City, with a case study of Dago Pojok Creative Village. In order to know this, the research approach used in this study is a qualitative approach, namely a case study, which emphasizes data collection and analysis using deductive logic. Data collection was carried out using two data sources, namely primary data through interviews and observation and secondary data. Based on the results of the analysis, it was found that the categories of actors/stakeholders who took part in the SOI development process consisted of 3 groups with 7 roles, namely the key interest group namely Rahmat Jabaril who had the role of initiator, stimulator, and impact extender. Furthermore, the support group consists of the Taboo Community who act as concept refiners, the Government of RT/RW/Bandung City who act as context enablers, and academics and researchers who act as educators. Furthermore, based on the results of actor network theory (ANT) analysis, it can be concluded that between actors have involvement which is described through an actor-network perspective to see clearer interactions and relationships between actors and their backgrounds involved in the development of SOI in Dago Pojok Creative Village. Based on all the results ofiv the analysis carried out, it can be concluded that based on the results of the analysis carried out, it can be concluded that there is an actor's role in the development of Sustainability Oriented Innovation (SOI) in Dago Pojok Creative Village. This research was conducted with a number of limitations so that improvements are still needed. There are several suggestions that can be given for further studies, namely as follows. In the future, further research can be carried out by analyzing several government parties and finding reasons for not implementing collaboration with Dago Corner Creative Village. Study of the important role of technology in multiactor networks, as a tool for recording and registering key resources